PENGEMBANGAN MODUL MATEMATIKA SMK TEKNOLOGI KELAS X SEMESTER GANJIL TERINTEGRASI PENDIDIKAN KARAKTER BANGSA - Putri Dian Wijayanti; Leny Hartati (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
The purpose of this research is to develop a mathematics learning module at a Vocational High Schools Technology group Class X Semester 1 which is effective to facilitate the learning process of mathematics by students independently as well as to instill some values of nation character through math learning, based on expert assessment and student response. Adaptation procedures from the Dick and Carey learning development model adapted into the module development stage written by the PMPTK covering module requirements analysis stage, draft module development, expert validation, classroom testing, and revision. Quality of Mathematics learning module at a Vocational High Schools Technology Class X Semester 1 based on expert evaluation is good. The student's response to the learning materials product is very positive. This Mathematics Module is expected to facilitate students of  Vocational High Schools especially Technological field in learning mathematics independently. Keywords:  Development, Mathematics Learning Module, Nation Character